A comparative study of ZnO-PVP and ZnO-PEG nanoparticles activity in membrane photocatalytic reactor (MPR) for industrial dye wastewater treatment under different membranes. Issue 3 (June 2019) - Desa, Amira Liyana; Hairom, Nur Hanis Hayati; Sidik, Dilaeleyana Abu Bakar; Misdan, Nurasyikin; Yusof, Norhaniza; Ahmad, Mohd Khairul; Mohammad, Abdul Wahab
Abstract: Membrane photocatalytic reactor (MPR) has gained immense research interest as valuable dye wastewater treatment over the conventional treatment due to its advantages. The effect of zinc oxide in the presence of polyethylene glycol (ZnO-PEG) nanoparticles in MPR under different membranes was studied in order to investigate the interaction of photocatalyst towards the degradation of industrial dye wastewater. The results revealed that ZnO-PEG nanoparticles and UF-PPA membrane are a great approach in MPR and produced good permeate quality in terms of SDWW degradation (100%), turbidity removal (100%), COD reduction (97.37 ± 0.06%) and electrical conductivity removal (92.38 ± 0.66%). Field Emission Scanning Electron Microscopy (FESEM) observation and contact angle analysis result confirmed that the presence of ZnO-PEG nanoparticles and UF-PPA membrane have great potential to improve fouling mitigation from being occurred in MPR. Hence, this research contributed a positive impact on the long-term use of water bodies and enhance the implementation of MPR for the industrial sector.